2018
DOI: 10.3389/fpls.2018.00050
|View full text |Cite
|
Sign up to set email alerts
|

Fagopyrum esculentum Alters Its Root Exudation after Amaranthus retroflexus Recognition and Suppresses Weed Growth

Abstract: Weed control by crops through growth suppressive root exudates is a promising alternative to herbicides. Buckwheat (Fagopyrum esculentum) is known for its weed suppression and redroot pigweed (Amaranthus retroflexus) control is probably partly due to allelopathic root exudates. This work studies whether other weeds are also suppressed by buckwheat and if the presence of weeds is necessary to induce growth repression. Buckwheat and different weeds were co-cultivated in soil, separating roots by a mesh allowing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 54 publications
5
30
3
3
Order By: Relevance
“…Common buckwheat can alter its root exudation after weed recognition and suppresses its growth, as was found for Amaranthus retroflexus (Gfeller et al 2018). Kumar et al (2008) reported that buckwheat residues in soil suppress Powell amaranth (Amaranthus powellii S.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Common buckwheat can alter its root exudation after weed recognition and suppresses its growth, as was found for Amaranthus retroflexus (Gfeller et al 2018). Kumar et al (2008) reported that buckwheat residues in soil suppress Powell amaranth (Amaranthus powellii S.…”
Section: Introductionmentioning
confidence: 81%
“…Despite many studies, there is no conclusive evidence of which compounds are directly responsible for the phenomenon of allelopathy in buckwheat. Probably, the whole set of compounds present in buckwheat tissues is involved in this phenomenon, along with microorganisms present in the soil (Gfeller et al 2018). Moreover, Kumar et al (2008) suggested that the mechanisms by which buckwheat residue can suppress weeds may include biological control of fungal pathogens and decreased nitrogen availability.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our results, S. alba has been shown to delay emergence of early-season weeds in potato, pea and soybean fields, 29,30 sinalbin from S. alba seeds inhibited germination of Stellaria media L. (98%) and Poa annua L. (73%) 31 and S. alba mulch reduced broadleaf weeds (83%) in sugar beet fields. 32,33 The strong allelopathic effects of S. alba may reflect its content of the allelochemicals glucotropaeolin (45 mg kg -1 ), glucosinalbin (7.2 mg kg -1 ) and glucobrassicin (<0.1 mg kg -1 ). 20 For example, hydrolysis products of glucosinolates, like isothiocyanates, can inhibit or delay germination.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon of anti‐microbial ‘cloud’ formation and RET spreading is expected to be amplified upon microbial attack or recognition of microbial‐derived elicitors by AC‐DCs. It could also be influenced by communication among plants in the rhizosphere, a well‐known process that occurs through allelochemicals, electric signals or mycorrhizal networks (Johnson & Gilbert, ; Gfeller et al , ; Gilroy, Trebacz & Salvador‐Recatalà, ).…”
Section: Dispersal and Diffusion Of Rets Into The Rhizosphere: ‘The Rmentioning
confidence: 99%